Novel biomaterials: plasma-enabled nanostructures and functions. (7th June 2016) - Levchenko, Igor; Keidar, Michael; Cvelbar, Uroš; Mariotti, Davide; Mai-Prochnow, Anne; Fang, Jinghua; Ostrikov, Kostya (Ken)
Abstract: Material processing techniques utilizing low-temperature plasmas as the main process tool feature many unique capabilities for the fabrication of various nanostructured materials. As compared with the neutral-gas based techniques and methods, the plasma-based approaches offer higher levels of energy and flux controllability, often leading to higher quality of the fabricated nanomaterials and sometimes to the synthesis of the hierarchical materials with interesting properties. Among others, nanoscale biomaterials attract significant attention due to their special properties towards the biological materials (proteins, enzymes), living cells and tissues. This review briefly examines various approaches based on the use of low-temperature plasma environments to fabricate nanoscale biomaterials exhibiting high biological activity, biological inertness for drug delivery system, and other features of the biomaterials make them highly attractive. In particular, we briefly discuss the plasma-assisted fabrication of gold and silicon nanoparticles for bio-applications; carbon nanoparticles for bioimaging and cancer therapy; carbon nanotube-based platforms for enzyme production and bacteria growth control, and other applications of low-temperature plasmas in the production of biologically-active materials.